(untitled) (Journal of Computational Mathematics, 1996)
This paper deals with Raviart-Thomas element (Q_2,1× Q_1,2-Q_1 element). Apart from its global superconvergence property of fourth order, we prove that a postprocessed extrapolation can globally increased the accuracy by fifth order.